Use of Audiobooks as an Environmental Distractor to Decrease State Anxiety in Children Waiting in the Pediatric Emergency Department: A Pilot and Feasibility Study - Stein Duker, Leah I.; Schmidt, Anita R.; Pham, Phung K.; Ringold, Sofronia M.; Nager, Alan L. (Frontiers in Pediatrics, 2021)
Objectives: Anxiety and anticipatory stressors are commonly experienced by children visiting the Pediatric Emergency Department (PED), but little research exists that addresses the efficacy of interventions to decrease this stress. This one-sample pretest-postest pilot study gathered preliminary data on the feasibility and effectiveness of utilizing audiobooks to reduce fear and state anxiety in children in the PED. Methods: Participants were 150 children in kindergarten through 8th grade, triaged urgent or emergent, presenting to the PED. Participants self-reported fear (Children’s Fear Scale) and state anxiety (modified State-Trait Anxiety Inventory for Children; mSTAIC) before and after listening to an age-appropriate audiobook (two options). Data regarding patient experience were also collected. Paired samples t-test was used to examine pre-post intervention changes in fear and state anxiety. Results: Significant, albeit small, improvements in fear and the mSTAIC states of nervous, calm, happy, and relaxed were found after use of the audiobook (Cohen's dz=0.22-0.35). Small yet significant correlations were found between child age/grade level and improvements in fear and in the mSTAIC states of scared and relaxed, suggesting that the audiobook was more beneficial for older participants. Over 60% of participants liked the audiobook content ‘a lot’ as well as enjoyed listening to the audiobook ‘a lot’. Without prompting, 15% of participants requested to listen to an additional audiobook. Conclusions: Listening to an audiobook is feasible and could be effective in decreasing fear and state anxiety for children during a waiting period in the PED. The technology is low-cost, simple, and portable.